Chemical composition and bioactivity of hemp, reed canary grass and common reed grown on boreal marginal lands - Fidelis, Marina; Tienaho, Jenni; Brännström, Hanna; Korpinen, Risto; Pihlava, Juha-Matti; Hellström, Jarkko; Jylhä, Paula; Liimatainen, Jaana; Möttönen, Veikko; Maunuksela, Jyri; Kilpeläinen, Petri (Royal Society of Chemistry (RSC), 2023)
Underutilised agricultural land and former peat production areas in northern Europe are potentially suitable for growing lignocellulosic biomass that could be used in various non-food applications. In this study, the biorefining process of Phalaris arundinacea (reed canary grass), Phragmites australis (common reed), and Cannabis sativa (oil and fibre hemp cultivars) was assessed based on their chemical composition and biological activity using various analytical techniques. Two-stage accelerated solvent extraction was used first with hexane, followed by EtOH/H2O (95/5, v/v) to extract the lipophilic and hydrophilic fractions of the samples collected during and after the growing season. Later, pressurised hot water extraction (PHWE) and two-stage extraction were performed to examine the biorefinery potential of aqueous extracts focusing on extraction efficiency, quality, and chemical composition of the plant materials. Combining two-stage and elevated extraction temperatures with PHWE resulted in high levels of total dissolved solids (TDS), carbohydrates, phenolics, and bioactivities. Data showed that TDS yielded over 400 mg g−1 for summer oil hemp and approximately 300 mg g−1 for reed canary grass and common reed. Summer-harvested plants had carbohydrate yields of 110–155 mg g−1, while autumn yields were 40–60 mg g−1 for hemp and 120–170 mg g−1 for reed canary grass and common reed, respectively. The findings suggest that aboveground biomass from marginal lands holds potential as a valuable source of bioactive compounds for biorefinery feedstocks, thereby presenting new opportunities for sustainable biomass-based valorisation and future optimisation of two-stage extraction methods targeting hemicellulose-rich fractions.